2016
DOI: 10.3177/jnsv.62.380
|View full text |Cite
|
Sign up to set email alerts
|

Daily Intake of Trehalose Is Effective in the Prevention of Lifestyle-Related Diseases in Individuals with Risk Factors for Metabolic Syndrome

Abstract: SummaryWe previously performed animal studies that suggested that trehalose potentially prevents the development of metabolic syndrome in humans. To evaluate this possibility, we examined whether trehalose suppressed the progression of insulin resistance in a placebo-controlled, double-blind trial in 34 subjects with a body mass index (BMI) $23. The subjects were divided into two groups and were assigned to ingest either 10 g/d of trehalose or sucrose with meals for 12 wk. During the study, body composition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…In previous reports, we showed that the intake of trehalose suppressed adipocyte hypertrophy and mitigated insulin resistance in mice fed a high-fat diet [ 3 , 4 ]. Additionally, we confirmed that the consumption of trehalose with a meal three times daily improved glucose tolerance and mitigated the progression of insulin resistance in humans [ 26 ]. Low secretion characteristics of GIP may contribute to the suppression of adipocyte hypertrophy and insulin resistance.…”
Section: Discussionsupporting
confidence: 67%
“…In previous reports, we showed that the intake of trehalose suppressed adipocyte hypertrophy and mitigated insulin resistance in mice fed a high-fat diet [ 3 , 4 ]. Additionally, we confirmed that the consumption of trehalose with a meal three times daily improved glucose tolerance and mitigated the progression of insulin resistance in humans [ 26 ]. Low secretion characteristics of GIP may contribute to the suppression of adipocyte hypertrophy and insulin resistance.…”
Section: Discussionsupporting
confidence: 67%
“…Some research studies demonstrated that daily intake of 10 grams of trehalose improve glucose tolerance and reduce the progress of insulin resistance. Furthermore, researchers suggested that trehalose can potentially reduce the development of metabolic syndrome and reduce other associated lifestyle-related diseases such as, type 2 diabetes [41]. The only, reported disadvantages from trehalose intake is the high glycemic index, and is not suitable for patients with active celiac diseases, or GLUT 1 deficiency syndrome, [42] a disorder affecting the nervous system that can have a variety of neurological signs and symptoms, (GLUT 1, is the protein that transport glucose across brain barrier).…”
Section: Trahalosementioning
confidence: 99%
“…Mammals do not store sugar as trehalose but do possess the enzyme trehalase to breakdown ingested trehalose (28). Further, oral supplementation of trehalose has been shown to improve glucose tolerance in individuals at high risk for developing type 2 diabetes (29) and can improve recovery from traumatic brain injury in mice (30).…”
mentioning
confidence: 99%